BUDAYA PERUSAHAAN DAN PERSEPSI PENGEMBANGAN KARIR PADA KARYAWAN YANG BEKERJA DI PT. TELEKOMUNIKASI INDONESIA - Melinda, Tina; Zulkarnain, - (Jurnal Psikologi, 2004)
The purpose of this study is to investigate the relationship between Corporate Culture and Perception of Carrier Development. The study was a field research which data collected through Scale of Corporate Culture and Scale of Perception of Carrier Development. The subject were employees of PT. Telekomunikasi Indonesia Divisi Regional I Sumatera (Medan). The result show that was a significant correlation between corporate culture and perception of carrier development (rxy = 0.833, p < 0.01). the correlation indicated that the strong corporate culture, the more positive perception of carrier development. In addition, the finding also shows there was no significant difference in perception of carrier development based on worked period (F = 2,193, p > 0.05) Keywords: Corporate Culture, Perception of Carrier development.